2020
DOI: 10.1038/s41467-020-18530-5
|View full text |Cite
|
Sign up to set email alerts
|

Frugivore-fruit size relationships between palms and mammals reveal past and future defaunation impacts

Abstract: Mammalian frugivores are critical seed dispersers, but many are under threat of extinction. Futhermore, the impact of past and future defaunation on plant assemblages has yet to be quantified at the global scale. Here, we integrate palm and mammalian frugivore trait and occurrence data and reveal a global positive relationship between fruit size and frugivore body size. Global variation in fruit size is better explained by present-day frugivore assemblages than by Late Pleistocene assemblages, suggesting ecolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 95 publications
4
60
0
Order By: Relevance
“…1.2 (Faurby and Svenning 2015, Faurby et al 2018). Our use of present natural ranges as proxies for ‘historical' distributions is similar to that of Belote et al (2020) and Lim et al (2020), but we employed a selection filter based on how these ranges were derived. In fact, present natural ranges represent species potential distributions in the absence of human modification, and they have been derived using a variety of techniques to estimate pre‐impact distributions of each species.…”
Section: Methodsmentioning
confidence: 99%
“…1.2 (Faurby and Svenning 2015, Faurby et al 2018). Our use of present natural ranges as proxies for ‘historical' distributions is similar to that of Belote et al (2020) and Lim et al (2020), but we employed a selection filter based on how these ranges were derived. In fact, present natural ranges represent species potential distributions in the absence of human modification, and they have been derived using a variety of techniques to estimate pre‐impact distributions of each species.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of megafruit dispersal by large-bodied animals have been conducted in ecosystems around the world, including savannas and drier forest patches (Campos-Arceiz et al, 2008;Sekar and Sukumar, 2013;Sridhara et al, 2016) and in tropical forests (Kitamura et al, 2007;Harich et al, 2016). Several recent studies have shown that the megafaunal extinctions caused a loss or complete termination of seed-dispersal processes in many arborescent plants (Guimarães et al, 2008;Galetti et al, 2017;McConkey et al, 2018;Onstein et al, 2018;Pires et al, 2018;Lim et al, 2020). FIGURE 3 | A timeline showing key coevolutionary processes that created mutualistic relationships between large mammals and crop and weed progenitors.…”
Section: Large Fleshy Fruiting Plantsmentioning
confidence: 99%
“…Onstein et al ( 2018 ) link megafaunal extinctions to an evolutionary decrease in the size of the fruits produced across the Arecaceae family and high rates of species extinctions throughout the Holocene (Lim et al, 2020 ). Purugganan ( 2019 ) used date palms ( Phoenix spp.)…”
Section: Lost Seed-dispersal Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the long-term, it leads to the functional erosion of plant traits related to reproduction that provide food resources for animals (Marcilio-Silva et al, 2016;Rocha-Santos et al, 2020). The loss of functional diversity of plant community might influence the availability and variability of floral, fruit, and seed resources for the associated fauna, thus increasing their vulnerability to future disturbances (Magnago et al, 2014;Pessoa et al, 2017a,b;Lim et al, 2020;Rocha-Santos et al, 2020). Specifically, in forest fragments embedded in highly deforested landscapes, the vegetation homogenization triggers a decrease in fruit biomass production and fruit quality (Pessoa et al, 2017a,b), possibly disrupting animal-plant interactions fundamental for the provision of ecological services (e.g., pollination and seed dispersal) (Mitchell et al, 2015;Valiente-Banuet et al, 2015).…”
Section: Introductionmentioning
confidence: 99%